Adoption of climate-smart agriculture in the peri-urban small towns of Kibaigwa and Dumila, Tanzania - Kauki, Boniface Gerald (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.